2016
DOI: 10.1016/j.psychres.2016.04.086
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of thought substitution on intentional forgetting in induced and naturally occurring dysphoria

Abstract: Two experiments were conducted to determine if natural and induced dysphoria is associated with impaired forgetting and, whether a thought-substitution strategy would ameliorate any observed deficits. Study 1: 36 dysphoric & 36 non-dysphoric participants learnt a series of emotional word pairs. Participants were subsequently presented with some of the cues and were asked to recall the targets or prevent the targets from coming to mind. Half of the participants were provided with substitute words to recall inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 53 publications
7
19
0
Order By: Relevance
“…Prior to the TNT task, participants were invited to complete the operation Span task (OSPAN; Turner & Engle, 1989 ). In line with our previous findings (Noreen & Ridout, 2016a , b ), we predicted that dysphoric participants would exhibit impaired suppression-induced forgetting of ‘to-be-forgotten’ words compared to non-dysphoric individuals. In line with Hubbard et al ( 2016 ), we expected that dysphoric participants would exhibit poorer working memory capacity (lower OSPAN scores) than would the non-dysphoric group.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…Prior to the TNT task, participants were invited to complete the operation Span task (OSPAN; Turner & Engle, 1989 ). In line with our previous findings (Noreen & Ridout, 2016a , b ), we predicted that dysphoric participants would exhibit impaired suppression-induced forgetting of ‘to-be-forgotten’ words compared to non-dysphoric individuals. In line with Hubbard et al ( 2016 ), we expected that dysphoric participants would exhibit poorer working memory capacity (lower OSPAN scores) than would the non-dysphoric group.…”
Section: Introductionsupporting
confidence: 86%
“…For example, Joormann et al ( 2009 ) used the TNT task and found that clinically depressed participants showed impaired forgetting of negative words. Impaired forgetting on the TNT has also been observed in participants with dysphoria (Hertel & Gerstle, 2003 ; Noreen & Ridout, 2016a , b ), although the deficit in these participants was not limited to negative words.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…First, growing evidence suggests that inhibitory processes engaged to suppress retrieval of unwanted memories reduce explicit memory for the suppressed events, contributing to a phenomenon known as suppression-induced forgetting ( Anderson & Green, 2001 ; see Anderson & Hanslmayr, 2014 for a review). Notably, difficulties in forgetting via retrieval suppression have been associated with worse mental health status: impaired suppression-induced forgetting has been found in individuals suffering from post-traumatic stress disorder ( Catarino, Kupper, Werner-Seidler, Dalgleish, & Anderson, 2015 ), high ruminators ( Fawcett et al, 2015 , Hertel et al, 2018 ), people with higher trait anxiety ( Marzi, Regina, & Righi, 2014 ; see also Benoit, Davies, & Anderson, 2016 ), and in participants suffering from depression ( Hertel and Gerstle, 2003 , Noreen and Ridout, 2016a , Noreen and Ridout, 2016b , Zhang et al, 2016 ). In contrast, better suppression-induced forgetting ability predicts reduced intrusiveness of a traumatic film over a one-week period ( Streb, Mecklinger, Anderson, Lass-Hennemann, & Michael, 2016 ) and also predicts reduced negative affect associated with suppressed content ( Gagnepain, Hulbert, & Anderson, 2017 ).…”
Section: Introductionmentioning
confidence: 99%